2014
DOI: 10.1097/aog.0000000000000186
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence, Depression, and Economic Outcomes in a Cohort of Women Between the Ages of 54 and 65 Years

Abstract: Objective To estimate the association between urinary incontinence and probable depression, work disability, and workforce exit. Methods The analytic sample consisted of 4,511 women enrolled in the population-based Health and Retirement Study cohort. The analysis baseline was 1996, the year that questions about urinary incontinence were added to the survey instrument, and at which time study participants were 54–65 years of age. Women were followed with biennial interviews until 2010–2011. Outcomes of intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 43 publications
(58 reference statements)
2
44
2
2
Order By: Relevance
“…Some working women have indicated that UI affected decisions about employment by a reduction of the number of hours worked or change in the type of work undertaken . UI in older women has been predictive of work disability (measured by self‐report of work limitations), but not workforce exit . Thus, findings of the current investigation have significant implications for the workforce.…”
Section: Discussionmentioning
confidence: 69%
“…Some working women have indicated that UI affected decisions about employment by a reduction of the number of hours worked or change in the type of work undertaken . UI in older women has been predictive of work disability (measured by self‐report of work limitations), but not workforce exit . Thus, findings of the current investigation have significant implications for the workforce.…”
Section: Discussionmentioning
confidence: 69%
“…This is important because several population‐based studies have shown a relationship between mental health and LUTS (Hung et al . , Lung‐Cheng Huang et al . ), although further studies are required to establish any causal links and investigate pathophysiological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Further, UI increased an individual's risk of work disability in a US follow‐up study of 4511 of women aged between 54–l65 years enrolled in the ‘Health and Retirement Cohort’ (Hung et al . ). These findings indicate the potential impact of PF dysfunction in a workforce.…”
Section: Introductionmentioning
confidence: 97%
“…Studies have established that depression and UI are often comorbid [10][11][12][13][14][15][16], but the role of depression as a cause or consequence of UI is less clear. Furthermore, previous studies have primarily focussed on mid-age and older women, with the result that much less is known of the aetiology of UI and links between depression and the condition among younger women [5].…”
Section: Introductionmentioning
confidence: 98%